Education on fulfilling balanced nutrition for pregnant women to improve nutritional status during pregnancy at bpm nooraeni kadir, s.st., gowa regency - Muldaniyah, Muldaniyah (CV. Paperhome Indonesia, 2024)
The nutritional needs of pregnant women must be fulfilled because the needs of pregnant women must be able to nourish the fetus in the womb. Do not let pregnant women lack nutrition because if they lack nutrition the fetus they contain is unhealthy and also has complications. The facts found in the field are that there is low public knowledge about the importance of nutrition in pregnant women. The method of solving problems that is carried out is Education about providing education on the importance of nutrition to pregnant women. During the community service activities, 20 pregnant women attended the attendance. The results of the activity were obtained. Participants were enthusiastic about the extension material, none of the participants left the extension site during the extension process and more than 75% of the participants who attended were able to answer questions from the extension agents about the material presented. This proves that the participants pay attention to the material presented. The conclusion is that the provision of knowledge about the importance of nutrition in pregnant women has a positive impact on society, so that people understand the importance of nutrition in pregnant women.